2018
DOI: 10.1016/j.ijpharm.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the association of dodecyl gallate with nanostructured lipid system as a treatment for paracoccidioidomycosis: In vitro and in vivo efficacy and toxicity

Abstract: Paracoccidioidomycosis (PCM) is a systemic mycosis endemic in Latin America, caused by Paracoccidioides spp. A limited number of antifungal agents are available and the search for new compounds has increased. Additionally, nanostructured lipid system (NLS) has emmerged as an interesting strategy to carrier compounds for the treatment of mycosis. In this work, the antifungal efficacy and toxicity of dodecyl gallate (DOD) associated with a NLS was evaluated through in vitro and in vivo tests. DOD showed good in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Our results showed that the incorporation of nonyl into NLS reduced toxicity in the embryos by 12.7 times, showing an increase in the therapeutic margin through incorporation. Similar results were obtained by Singulani et al (2018), when the compound derived from gallic acid, dodecyl gallate was incorporated into an NLS using another surfactant, Brij R 35.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our results showed that the incorporation of nonyl into NLS reduced toxicity in the embryos by 12.7 times, showing an increase in the therapeutic margin through incorporation. Similar results were obtained by Singulani et al (2018), when the compound derived from gallic acid, dodecyl gallate was incorporated into an NLS using another surfactant, Brij R 35.…”
Section: Discussionsupporting
confidence: 75%
“…The NLS characterization tests showed that the incorporation of nonyl into the NLS caused a small variation in the size of the particles. The values obtained are in the range from 10 to 250 nm (100-2500 Å), which is considered an ideal range for nanostructured lipid systems of the microemulsion type, according to Formariz et al (2005) and Singulani et al (2018). When comparing the control formulation (NLS) and the formulation containing the incorporated compound (NLS + nonyl), there is a small increase in the size of the particles, which is a strong indication that the sample has been incorporated into the lipid system.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For this, cells were separated in two groups: (i) cells with only one or without any buds and (ii) cells with more than one bud. In the CFU enumeration assay, an aliquot of 100 l was diluted (1:100) in PBS and plated on solid BHI medium supplemented with 4% fetal calf serum, 5% P. brasiliensis (strain 192)-spent culture medium, 1.5% glucose, and gentamicin (40 mg/ml) and incubated at 37°C for 15 days, and colonies were counted (46). For the MTT assay, the 96-well plate was centrifuged for 2 min at 5,000 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 15 g/ml of ketoconazole (Sigma) in DMEM was added for 1 h at 37°C to kill only the adhered fungi, followed by PBS washes to remove them. The A549 cells were lysed with 100 l of sterile MilliQ water (32), and the suspension was plated on solid BHI medium supplemented as described previously and incubated at 37°C for 15 days for colony counts (46). The CFU count obtained indicates fungal cells that were internalized.…”
Section: Methodsmentioning
confidence: 99%